Peran Perguruan Tinggi Dalam Penanaman Dan Penguatan Pendidikan Karakter Dan Anti Korupsi - Achmad Asfi Burhanudin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
Until now, the practice of criminal acts of corruption is still rife by elements in our beloved country. Even though the government and DPR have formed regulations and institutions to eradicate corruption, in practice there are still corrupt practices. One of the efforts to reduce the rampant corruption in Indonesia is by involving universities. Anti-corruption education is considered to be one of the strategies for eradicating corruption because it can create an anti-corruption cultural ecosystem in building the character of the younger generation. On the other hand, Higher Education can instill the value of integrity which can be embodied through the Tri Dharma of Higher Education which includes education, research, and community service. The method used in this research is through a literature study by taking an inventory of all the sources of literature used and then carefully verifying it to ensure the level of relevance of the material collected to the object that is the focus of study in research. The study of literature aims to find answers about the Role of Higher Education in Planting and Strengthening Character Education and Anti-Corruption. The role of tertiary institutions is in terms of preventing corruption, especially in cultivating anti-corruption attitudes and anti-corruption characters, increasing legal awareness, and instilling integrity values ​​in students. Students who are future leaders of the nation need to be fortified to avoid corrupt behavior and acts of corruption. For this reason, optimizing the Tri Dharma of Higher Education is an effort to foster an anti-corruption attitude for students and the community.